Precentral and cerebellar atrophic changes in moyamoya disease using 7-T magnetic resonance imaging. (April 2020) - Moon, Hyeong Cheol; Oh, Byeong Ho; Cheong, Chaejoon; Kim, Won Seop; Min, Kyung Soo; Kim, Young Gyu; Park, Young Seok
Background: Chronic repeated transient ischemic changes are one of the common symptoms of moyamoya disease that could affect cortical and subcortical atrophy. Purpose: We aimed to assess the cortical gray matter volume and thickness, white matter subcortical volume, and clinical characteristics using 7-T magnetic resonance imaging (MRI) and MR angiography (MRA). Material and Methods: In this case-control study, whole-brain parcellation of gray matter and subcortical volumes were manually assessed in nine patients with moyamoya disease (18 hemispheres; median age = 34 years; age range = 10–60 years) and nine healthy controls (18 hemispheres; median age = 29 years; age range = 20–62 years) matched for age and sex, who underwent both 7-T MRI and MRA. The volumes were measured using high-resolution image (<1 mm) processing based on the Desikan-Killiany-Tourville (DKT) atlas, via an automated segmentation method (FreeSurfer version 6.0). Results: The gray matter volume of the left precentral cortex and the white matter volume of the subcortical cerebellum were lower in both hemispheres in the patients with moyamoya disease compared to the healthy controls. Conclusion: Gray matter atrophy in the precentral cortex and cerebellar white matter were detected in this 7-T MRI volumetric analysis study of patients with moyamoya disease who experienced repeated transient ischemic changes. Cortical atrophy in precentral cortex and cerebellum could explain the transient motor weakness in patients with moyamoya disease, as one of the early findings was that patients with moyamoya disease do not have detectable infarction changes on conventional MRI images.